HUBUNGAN MOTIVASI TERHADAP HASIL BELAJAR MAHASISWA PENDIDIKAN BIOLOGI UNIVERSITAS MAHAPUTRA MUHAMMAD YAMIN PADA MATA KULIAH PERKEMBANGAN PESERTA DIDIK TAHUN AKADEMIK 2018/2019 - Roza, Helvita; Sepyanda, Marsika (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The purpose of this study is to find out the extent of the relationship of motivation to the learning outcomes of students of biaputra muhammad yamin university in the development subject of participants students in the academic year 018/2019. This type of research is descriptive. The population and sample of this study were 10 students in biology education semester II of Academic Year 018/2019. Data were collected using a motivational questionnaire consisting of 0 items. The data obtained is processed using simple linear correlation techniques. From the test r obtained by the price of the correlation coefficient r count = 0.3835 and r table = 0.320 then r count> r table means there is a positive and significant relationship of 0.3835. From the t test, it was obtained tcount = .49 and ttable = .02, it means tcount> ttable in the sense that there was a significant relationship between motivation and learning outcomes of biology education students at the university of mahaputra muhammad yamin in the subject of student development in the academic year 018/2019 on a 95% confidence level. The price of the determinant coefficient = 14.71% then the relationship of motivation with learning outcomes is very low. This means that student learning outcomes 14.71% is determined by motivation, the remaining 85.29% is determined by other factors.